CONHECIMENTOS DE HOMENS SOBRE VIOLÊNCIA CONTRA MULHER: UMA REVISÃO INTEGRATIVA - Gonçalves, Wallace Almeida; Bezerra, Luca Victor Freire; Souza , Isa Clara Andrade; da Silva, Renilda Mayane Lopes; Simões, Aline Vieira; Machado, Juliana Costa (Encontro sobre violência intrafamiliar, 2024)